2020
DOI: 10.1175/mwr-d-19-0402.1
|View full text |Cite
|
Sign up to set email alerts
|

Local Ensemble Transform Kalman Filter with Cross Validation

Abstract: Many ensemble data assimilation (DA) approaches suffer from the so-called inbreeding problem. As a consequence, there is an excessive reduction in ensemble spread by the DA procedure, causing the analysis ensemble spread to systematically underestimate the uncertainty of the ensemble mean analysis. The stochastic EnKF used for operational NWP in Canada largely avoids this problem by applying cross validation, that is, using an independent subset of ensemble members for updating each member. The goal of the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Along with localization, covariance inflation is an indispensable component of practical EnKF implementation, unless some special measure like the cross‐validation technique (Houtekamer and Mitchell, 1998; Houtekamer et al ., 2009; Buehner, 2020) is employed. Despite its importance, covariance inflation is often performed in an ad hoc manner.…”
Section: Discussion: Interpretation Of Results From the Literature Inmentioning
confidence: 99%
See 3 more Smart Citations
“…Along with localization, covariance inflation is an indispensable component of practical EnKF implementation, unless some special measure like the cross‐validation technique (Houtekamer and Mitchell, 1998; Houtekamer et al ., 2009; Buehner, 2020) is employed. Despite its importance, covariance inflation is often performed in an ad hoc manner.…”
Section: Discussion: Interpretation Of Results From the Literature Inmentioning
confidence: 99%
“…Cross‐validation cannot be applied straightforwardly to square‐root filters like the ETKF‐based family of EnKFs and its application has been limited to stochastic EnKF, in which each member is updated independently by assimilating perturbed observations. A recent study by Buehner (2020) showed, however, that cross‐validation can be combined with LETKF by using the gain‐form representation of ETKF (Bishop et al ., 2017) and that cross‐validation does mostly alleviate analysis underdispersion using both idealized experiments and a realistic regional NWP system. Throughout the current article, we have limited our scope to analyzing ETKF and its variants, and the framework developed here cannot deal with the cross‐validation approach.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…This may have been the result of the filter estimate becoming statistically overconfident relative to the magnitude of the measurement residuals, or one of the ensemble ionospheres may not have been suitable for LWPC. Underestimation of the state covariance by EnKFs is an active research area, but may be improved in future work by implementing additive covariance inflation between iterations or cross validation of the ensemble members in the LETKF measurement update (Buehner, 2020; Houtekamer & Zhang, 2016). If LWPC is the problem, it could be replaced with LMP as the LETKF forward model because LMP is more robust to atypical ionosphere profiles.…”
Section: Simulated Observation Experimentsmentioning
confidence: 99%